Glaucoma in Developing Countries - Thapa, Suman Shumshere; Paudyal, Indira; Joshi, Pratibha Lama; Singh, Kalpana; Parajuli, Anil (Nepalese Journal of Ophthalmology, 2021)
Glaucoma is a leading cause of blindness worldwide. The diagnosis and management of glaucoma is especially difficult in the developing countries. Lack of cost effective screening strategies, low income, low rates of literacy and inadequate infrastructures and human resources for eye care services are the obstacles for delivering glaucoma service. Majority of people with glaucoma in developing countries usually present at an advanced stage at the time of diagnosis; which negatively affects their quality of life. Further research, proper allocation of resources and collaborative effort by blindness prevention programs will hopefully provide new evidences on cost effective ways to screen and manage glaucoma in the future. This article aims to highlight the burden of glaucoma and ways to address the challenges in developing countries.